AMIC Cartilage Repair in a Professional Soccer Player - S. Bark; H. Riepenhof; J. Gille (Case Reports in Orthopedics)
We report a case of a professional soccer player suffering from a traumatic cartilage lesion grade IV according to the Outerbridge classification at the femoral condyle treated with an enhanced microfracture technique (AMIC). Autologous Matrix-Induced Chondrogenesis (AMIC) is an innovative treatment for localized full-thickness cartilage defects combining the well-known microfracturing with collagen scaffold and fibrin glue. Because of the cartilage lesion (3 cm2), an AMIC procedure was performed followed by a rehabilitation program according to the protocols in the literature, (Steadman et al.; 2003). After 8 months of rehabilitation, the player returned to team training and after 10 months to competition. Altogether he returned to the same skill level for almost one year after the index operation. He is very satisfied with the clinical results after AMIC, which corresponds with the Lysholm score of 90 points at 12 months.